Size-dependent density of zirconia nanoparticles - Opalinska, Agnieszka; Malka, Iwona; Dzwolak, Wojciech; Chudoba, Tadeusz; Presz, Adam; Lojkowski, Witold (Beilstein Journal of Nanotechnology, 2015)
The correlation between density and specific surface area of ZrO2 nanoparticles (NPs) was studied. The NPs were produced using a hydrothermal process involving microwave heating. The material was annealed at 1100 °C which resulted in an increase in the average grain size of the ZrO2 NPs from 11 to 78 nm and a decrease in the specific surface area from 97 to 15 m2/g. At the same time, the density increased from 5.22 g/m3 to 5.87 g/m3. This effect was interpreted to be the result of the presence of a hydroxide monolayer on the NP surface. A smaller ZrO2 grain size was correlated with a larger contribution of the low density surface layer to the average density. To prove the existence of such a layer, the material was synthesized using 50% heavy water. Fourier transform infrared spectroscopy (FTIR) permitted the identification of the –OD groups created during synthesis. It was found that the –OD groups persisted on the ZrO2 surface even after annealing at 1100 °C. This hydroxide layer is responsible for the decrease in the average density of the NPs as their size decreases. This study of the correlation between particle size and density may be used to assess the quality of the NPs. In most cases, the technological aim is to avoid an amorphous layer and to obtain fully crystalline nanoparticles with the highest density possible. However, due to the effect of the surface layers, there is a maximum density which can be achieved for a given average NP diameter. The effect of the surface layer on the NP density becomes particularly evident for NPs smaller than 50 nm, and thus, the density of nanoparticles is size dependent.
Keywords: density; hydrothermal synthesis; hydroxy groups; nanometrology; nanopowders; zirconia